SOSIALISASI DETEKSI DINI IBU HAMIL DENGAN KEKURANGAN ENERGI KRONIK DI LINGKUP KOMUNITAS WILAYAH KERJA PUSKESMAS CEMPAKA MULIA KOTAWARINGIN TIMUR - Alestari, Rena Oki; Widia, Lidia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Early detection of pregnancy in pregnant women with Chronic Energy Deficiency (KEK) by measuring the circumference of the upper arm during pregnancy checks. The purpose of this health socialization is for pregnant women to understand early detection of pregnant women with KEK. The Community Service Method uses counseling using lectures, Q&A and monitoring of Lila measurements using Leaflet media and continuous Lila measurement and monitoring, the activity was carried out on March 23, 2025. Located in the working area of ​​the Cempaka Mulia Health Center, East Kotawaringin. The results of this community service can be said to be successful, this is observed in the level of attendance, activeness of participants. This activity took place in an orderly and good manner without experiencing significant obstacles. The follow-up that needs to be done is to continuously provide information about early detection of pregnant women with KEK to pregnant women.